Disturbed ratio of erythrocyte and plasma S-adenosylmethionine/S-adenosylhomocysteine in peripheral arterial occlusive disease - Loehrer, Franziska; Tschöpl, Martin; Angst, Christian Peter; Litynski, Piotr; Jäger, Kurt; Fowler, Brian; Haefeli, Walter E. (Atherosclerosis, 2001)
Altered homocysteine metabolism associated with peripheral arterial occlusive disease (PAOD) may lead to impairment of vital methylation reactions through accumulation of S-adenosylhomocysteine (AdoHcy) as well as through alteration of the ratio S-adenosylmethionine (AdoMet)/AdoHcy. We determined AdoMet, AdoHcy, their ratio, and homocysteine in plasma as well as AdoMet, AdoHcy, and their ratio in erythrocytes of 61 patients with PAOD (age 49-93) and 50 healthy controls (age 41-87). Geometric mean values of plasma homocysteine, AdoMet, and AdoHcy were significantly increased in patients compared with controls (15.5 vs. 10.4 μmol/l**; 107 vs. 52.3* nmol/l; 55.0 vs. 23.1** nmol/l, respectively; *P<0.01, **P<0.001), while the ratio of AdoMet/AdoHcy was decreased in patients (1.92 vs. 2.52*). In erythrocytes patients exhibited increased levels of AdoHcy compared with controls (309 vs. 205 nmol/l**) whereas AdoMet (3351 vs. 3732 nmol/l*) and the ratio of AdoMet/AdoHcy (11.8 vs. 19.1**) were decreased. The odds ratio (OR) for developing PAOD with decreased AdoMet/AdoHcy ratio after adjustment for kidney function was significant for erythrocyte levels ≤14.2 (OR, 7.1 (6.9-7.2, 95% CI). In addition, hematocrit levels were found to be significantly decreased in patients versus controls (0.35 vs. 0.42 l/l**) and were significantly correlated with the ratio of AdoMet/AdoHcy in erythrocytes of the patients. Since the ratio of AdoMet/AdoHcy is closely linked with the activity of numerous enzymatic methylation reactions, these results suggest that methylation may be impaired in these patients.